Case report: JAKi and TNFi dual therapy is a potential treatment strategy for difficult-to-treat rheumatoid arthritis - Chen, Jing-Wen; Zhang, Wen-Shuang; Lin, Chang-Song; Xu, Qiang (Frontiers in Immunology, 2022)
Rheumatoid arthritis (RA) is a heterogeneous chronic disease. RA patients should start disease modifying anti-rheumatic drugs (DMARDs) therapy immediately after diagnosis. If first-line treatment with conventional synthetic DMARDs does not relieve the disease, biology and targeted synthetic DMARDs are options for patients. Patients can switch to different types of biological and targeted synthetic DMARDs if remission is not achieved. However, for patients with difficult-to-treat RA, achieving disease stabilization after the failure of multiple biological and targeted synthetic DMARDs is a clinical challenge that needs to be addressed. As distinct cytokine pathways, the benefits and challenges of dual therapy are worth discussing. As the most extensively used biologic DMARDs, adalimumab is an anti-tumor necrosis factor monoclonal antibody used to treat RA. Tofacitinib, as a Janus Kinase inhibitor, is an orally administered targeted synthetic DMARDs that involved in the regulation of immune responses by directly or indirectly inhibiting cytokine pathways. This report describes a successful case of a 48-year-old woman with difficult-to-treat RA who treated with Tofacitinib combined with adalimumab. She had been on glucocorticosteroid for a long time, but had persistent joint pain and fatigue. At more than one year of follow-up, her Disease Activity Score for 28-joint counts based on the erythrocyte sedimentation rate (DAS28-ESR) remained in complete remission, and she discontinued her glucocorticosteroid medications. Also, she did not develop a mycobacterial tuberculosis infection, herpes zoster, and new-onset cardiovascular events.